2014
DOI: 10.1074/jbc.m114.555441
|View full text |Cite
|
Sign up to set email alerts
|

Solution Structure of the Ubiquitin-associated (UBA) Domain of Human Autophagy Receptor NBR1 and Its Interaction with Ubiquitin and Polyubiquitin

Abstract: Background:The autophagic receptor NBR1 is commonly found in ubiquitin-positive inclusions in neurodegenerative diseases. Results: Molecular recognition of ubiquitin and polyubiquitin by NBR1 is described. Conclusion:The ubiquitin-associated domain of NBR1 shows unexpectedly high affinity for monoubiquitin but lacks polyubiquitin linkage specificity. Significance: NBR1 may be highly efficient at forming intracellular inclusions with ubiquitylated proteins via non-linkagespecific association with ubiquitin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
59
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(63 citation statements)
references
References 42 publications
4
59
0
Order By: Relevance
“…In Ddi1UBA, the most perturbed residues are clustered around Gly402, located in the loop between helices 1 and 2, Glu420 and Ala423 in helix 3, and Phe427 at the C terminus (Fig 4D–E). The analysis of NMR titration curves from this titration yielded the dissociation constant K d of 150 ± 16 μM (Fig 4C, F), which is in the typical K d range (4–500 μM) reported for interactions between monomeric Ub and other UBA domains (Ohno et al, 2005; Raasi et al, 2005; Trempe et al, 2005; Varadan et al, 2005; Walinda et al, 2014; Zhang et al, 2008). Based on the CSP data from Ub:Ddi1UBA titrations, complemented with intermolecular distance constraints derived using site-directed paramagnetic spin-labeling (Fig S5), we generated a structural model of the Ub:Ddi1UBA complex using biomolecular docking program HADDOCK (de Vries et al, 2010).…”
Section: Resultsmentioning
confidence: 61%
“…In Ddi1UBA, the most perturbed residues are clustered around Gly402, located in the loop between helices 1 and 2, Glu420 and Ala423 in helix 3, and Phe427 at the C terminus (Fig 4D–E). The analysis of NMR titration curves from this titration yielded the dissociation constant K d of 150 ± 16 μM (Fig 4C, F), which is in the typical K d range (4–500 μM) reported for interactions between monomeric Ub and other UBA domains (Ohno et al, 2005; Raasi et al, 2005; Trempe et al, 2005; Varadan et al, 2005; Walinda et al, 2014; Zhang et al, 2008). Based on the CSP data from Ub:Ddi1UBA titrations, complemented with intermolecular distance constraints derived using site-directed paramagnetic spin-labeling (Fig S5), we generated a structural model of the Ub:Ddi1UBA complex using biomolecular docking program HADDOCK (de Vries et al, 2010).…”
Section: Resultsmentioning
confidence: 61%
“…The autophagy adaptor protein NBR1 also has a C-terminal UBA domain [53], and the NBR1 UBA domain binds to ubiquitin with higher affinity (K D = 3-4 μM) compared to the p62 UBA domain (K D = 540-750 μM) in vitro [49,54]. The difference in ubiquitin affinity is attributed to structural differences of the UBA domains in each protein.…”
Section: Discussionmentioning
confidence: 96%
“…The UBA domain contains the evolutionarily conserved MGF motif, and the charge of the amino acid residue immediately upstream of the MGF motif plays a crucial role in the interaction with ubiquitin [53]. Among UBA domains in the SMART database, 42% have a negatively charged amino acid residue at the position in front of the MGF motif, and the corresponding amino acid of NBR1 is the negatively charged at glutamic acid 926 [53]. In contrast, at the equivalent site of p62, serine 403 is uncharged.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the high architectural similarity between NBR1 and p62, both p62 and NBR1 have been reported to act cooperatively to target polyubiquitylated aggregates and whole organelles, including peroxisomes, to be selectively degraded [48,49]. Unexpectedly, Walinda et al [50] found that NBR1 differs from p62 in its UBA structure and accordingly in its interaction with ubiquitin. These differences result in a much higher affinity of NBR1 for ubiquitin than p62.…”
Section: Nbr1mentioning
confidence: 99%